2021
DOI: 10.7759/cureus.17928
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondral Injury of the Talus Treated With Cell-Free Hyaluronic Acid-Based Scaffold (Hyalofast®) – A Reliable Solution

Abstract: Bajuri et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…No associations, however, were identified between body mass index or lesion size and outcome scores [13]. Good outcomes with the use of the Hyalofast ® graft have also been reported in the treatment of chondral injuries of other joints [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…No associations, however, were identified between body mass index or lesion size and outcome scores [13]. Good outcomes with the use of the Hyalofast ® graft have also been reported in the treatment of chondral injuries of other joints [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…The chondral injury was debrided and treated with microfracture and application of cell-free hyaluronic acid-based scaffold (Hyalofast®) to stimulate new cartilage growth. A study of seven patients with osteochondral lesion grade III and IV of the tali that were treated with the same method showed significant improvement of physical function at one year post surgery [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study we have shown the generation of a 3D paracrine construct based on WJ-MSCs and HyaloFast ® using xeno-free clinically-acceptable conditions, and we propose a way to preserve the viability and the paracrine properties of the cells for a period of 6 days, as required to complete sterility testing. We chose HyaloFast ® as a 3D scaffold due to its high applicability in clinical applications, and also its confirmed biocompatibility and biodegradation [17,18,28,29]. HyaloFast ® is based on a semisynthetic insoluble polymer obtained by the esterification of all carboxyl groups of HA with benzyl alcohol (HYAFF-11 ® ).…”
Section: Discussionmentioning
confidence: 99%